A Rare Case Of Perioperative Methemoglobinemia In A Paediatric Child: A Case Report - Mohamad Azlan Awang; Muhamad Rafiqi Hehsan (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by Scopus